Seletividade de fungos entomopatogênicos e óleos essenciais a Apis mellifera L. (Hymenoptera: Apidae) - Colombo, Fernanda Caroline (2019)
Africanized Apis mellifera L. 1758 (Hymenoptera: Apidae) bees are social insects, considered useful due to their importance for agroecosystems. However, they are suffering from the colony collapse disorder and, among the suspects, stand out the synthetic chemical insecticides. Thus, as an alternative, there is the biological and alternative control of pests, however, the effects of entomopathogens and essential oils on bees are still scarced. Thus, he objective of this study was to evaluate the effect of the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae and the essential oils of Eugenia uniflora and Pogostemon cablin on africanized A. mellifera workers. For this, in the laboratory, four bioassays were performed with the entomopathogenic fungi (1×108 conidia.ml-1) and with the essential oils (0,75%): 1) A. mellifera contact on pulverized vitreous surface; 2) Contact of A. mellifera with treated eucalyptus leaves; 3) Direct spraying on A. mellifera and 4) Ingestion of candy paste incorporated with the treatments. The workers’ longevity was evaluated from one to 240 hours. For the queens’ production, two cycles were performed: 1) B. bassiana (1×108 conidia.ml-1) and sterilized distilled water and 2) M. anisopliae (1×108 conidia.ml-1) and sterilized distilled water For this, the transfer of larvae from workers to acrylic cupules containing royal jelly incorporated with the treatments was performed, with the emergence of the queens monitored and morphometric analyzes executed. In addition, gas chromatography of the essential oils was performed to verify the major compounds of these oils. Beauveria bassiana caused reduction in the workers’ longevity only in the direct spray bioassay and Metarhizium anisopliae caused reduction in the four bioassays tested. Essential uniflora essential oil caused a reduction in bees' longevity through direct spray and ingestion of candy paste and P. cablin reduced the longevity of A. mellifera in contact bioassays in eucalypt leaves, direct spray and ingestion of candy paste, when compared to workers from the control. In the queens’ production there was no reduction or interference in the morphometric parameters evaluated after ingestion of royal jelly incorporated with B. bassiana and M. anisopliae, nor in the emergency time when compared to queens from the control. The major compounds found in the E. uniflora essential oil were calamen-10-one, silfiperferol-6-em-5-one, germacron, germacrene B and the compounds found in the essential oil of P. cablin were patchoulol, α-guaene and γ-patchoulene. M. anisopliae and the essential oils of E. uniflora and P. cablin are not selective to A. mellifera when laboratory bioassays are performed, while B. bassiana can be considered selective. However, B. bassiana and M. anisopliae, in the field, were selective and safe for the production of A. mellifera queens. New tests, with different fungal isolates and different concentrations of the treatments, and in the field, are recommended.